PENGARUH PENGALOKASIAN BEASISWA BIDIKMISI, LINGKUNGAN TEMAN SEBAYA, DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR MAHASISWA BIDIKMISI TAHUN MASUK 2011 DI UNIVERSITAS NEGERI PADANG - Diliza Afrila (Jurnal Ilmiah Dikdaya, 2018)
This research aimed to analyze (1) The influence of bidikmisi scholarship allocation (cost to support study) to the learning result of  bidikmisi students at the academic year 2011 at State University of Padang, (2) The influence of peers to the learning result of bidikmisi students at the academic year 2011 at State University of Padang, (3) The influence of learning habit to the learning result of bidikmisi students at the academic year 2011 at State University of Padang, and (4) The influence of bidikmisi scholarship allocation (cost to support study), peers, and learning habit to the learning result of  bidikmisi students at the academic year 2011 at State University of Padang. This is a quantitative descriptive research, which consists of three independent variables and one dependent variable. There are 500 students as the population of this research.  The proportional random sampling technique is used to choose the sample. There are 87 bidikmisi students of the academic year 2011 as the research sample. The data collected by distribution of questionnaire to the research respondent and documentation of IPK each of research respondent taken from BAAK. The technique of data analysis is multiple regression with SPSS program Version 16. The research result shows that (1) Bidikmisi scholarship allocation (cost to support study) a significant influence to the learning result of  bidikmisi students at the academic year 2011 at State University of Padang. (2) Peers a significant influence to the learning result of bidikmisi students at the academic year 2011 at State University of Padang, (3) Learning habit a significant influence to the learning result of bidikmisi students at the academic year 2011 at State University of Padang, and (4) Bidikmisi scholarship allocation (cost to support study), peers, and learning habit a significant influence to the learning result of bidikmisi students at the academic year 2011 at State University of Padang. Keyword:  Pengalokasian Beasiswa Bidikmisi, Lingkungan Teman Sebaya, Kebiasaan Belajar, Hasil Belajar